2007
DOI: 10.1530/eje-07-0378
|View full text |Cite
|
Sign up to set email alerts
|

Insulin gene variable number of tandem repeats is not associated with weight from fetal life until infancy: the Generation R Study

Abstract: Objective: The aim of this study was to examine whether the insulin gene variable number of tandem repeats (INS VNTR) is associated with growth patterns in fetal life and infancy. Design and methods: This study was embedded in the Generation R Study, a population-based prospective cohort study from fetal life until young adulthood. Fetal growth was assessed by ultrasounds in early, mid-, and late pregnancy. Anthropometry in infancy was assessed at birth and at the ages of 6 weeks, 6 months, and 14 months. DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
(57 reference statements)
3
14
1
Order By: Relevance
“…Among SGA children, similarly to results provided by others [14][15][16][17][18], we did not find any relationship as regards the examined variants of INS VNTR and birth weight or birth length. Although Lindsay et al [10] have reported that the class III allele is associated with a reduction of birth weight, we should be aware that the analysis was performed among Pima Indians, in whom high incidence of obesity, IR, and T2DM is observed, and the distribution of birth weight may be associated with these maternal factors.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among SGA children, similarly to results provided by others [14][15][16][17][18], we did not find any relationship as regards the examined variants of INS VNTR and birth weight or birth length. Although Lindsay et al [10] have reported that the class III allele is associated with a reduction of birth weight, we should be aware that the analysis was performed among Pima Indians, in whom high incidence of obesity, IR, and T2DM is observed, and the distribution of birth weight may be associated with these maternal factors.…”
Section: Discussionsupporting
confidence: 88%
“…It was proven that both in foetal and in adult pancreas, lower insulin mRNA expression in INS VNTR class III homozygous than in class I homozygous individuals is observed [6,7,9]. However, the potential effect of class III allele on birth weight is still controversial [10][11][12][13][14][15][16][17][18]. On the other hand, class III is protective against diabetes mellitus type 1 (T1DM) and leads to an overexpression of insulin [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Also, strategies for genetic scoring analyses are being developed to estimate predictive values of identified genetic variants [171,172]. Although a GWAS is available in children, we use DNA from both children and parents for genotyping for candidate gene or replication studies [173][174][175][176][177][178][179][180][181][182]. Missing data in DNA samples in children will be collected by blood sampling or other methods at follow-up measurements.…”
Section: Biological Samplesmentioning
confidence: 99%
“…Several studies have suggested that this polymorphism is associated with size at birth, childhood and adult obesity, type 2 diabetes and insulin resistance [3,4,5]. However, thus far, findings seem to be rather inconsistent [1,4,6]. We have previously found an association of INS VNTR with a gestational duration but not with birth weight [4].…”
Section: Introductionmentioning
confidence: 95%
“…INS VNTR is known to have functional effects on circulating insulin levels, which may influence fetal and early postnatal growth [2]. Several studies have suggested that this polymorphism is associated with size at birth, childhood and adult obesity, type 2 diabetes and insulin resistance [3,4,5]. However, thus far, findings seem to be rather inconsistent [1,4,6].…”
Section: Introductionmentioning
confidence: 99%